Incidence and clinical characteristics of patients with torsades de pointes complicating acquired atrioventricular block. (19th May 2022) - Bun, S-S; Heme, N; Taghji, P; Asarisi, F; Squara, F; Scarlatti, D; Moceri, P; Deharo, JC; Ferrari, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Female gender, degree of QT prolongation and genetic susceptibility are known risk factors for developing torsade de pointe (TdP) during high-degree atrioventricular block (HD-AVB). Objective: To analyze the incidence and clinical characteristics of patients presenting with TdP and AVB (TdP [+]) in comparison with non-TdP patients with AVB (TdP [-]). Methods: All the ECG from patients prospectively admitted for advanced AVB (2 to 1 and complete) at our university hospital were analyzed. Automated corrected QT (QTc), and manual measurements of QT and JT intervals, and Tpeak-Tend were performed at the time of most severe bradycardia. Results: From Sept 2020 to Nov 2021, 100 patients were admitted for HD-AVB. Among them, 17 patients with TdP were identified (8 men; 81 ± 10 years). No differences could be identified concerning automated QTc, manual QTc (Bazett correction), baseline QRS width and mean left ventricular ejection fraction between the two groups. Potassium serum level on admission and mean number of QT-prolongating drugs per patient were not significantly different between the two groups, respectively: 4.34 ± 0.5 in TdP [+] versus 4.52 ± 0.6 mmol/L (p = 0.33); and 0.6 ± 0.7 in group A versus 0.5 ± 0.7 (p = 0.15). In contrast, manual QTcFR (Fridericia correction), corrected JT, Tpeak-to-end and Tpe/QT ratio were significantly increased in the TdP [+] group: respectively 486 ± 70 versus 456 ± 53 ms (p = 0.04); 433 ± 98 versus 381 ± 80 (p = 0.02); 153 ± 57 versus 110 ± 40 (p < 0.001); 0.27 ± 0.08 versus 0.22 ± 0.06 (p < 0.001). Conclusion: The incidence of TdP complicating acquired AVB was 17 % in a medium-volume center. Longer QTc (Fridericia), corrected JT and Tpeak-to-end were electrocardiographic predictors of TdP, while no clinical characteristics may predict the occurrence of this complication.